TEACHING MATERIALS FOR CHILDREN LITERATURE BY USING A PROCESS APPROACH - Citra Nur Faidah (Jurusan Sastra Indonesia, 2019)
Children's literature teaching materials are materials or learning materials are arranged systematically used teachers, lecturers and instructors and students, as well as students in KBM used for children's literature learning. Children's literature teaching materials mainly deal with literature related to children. both in terms of theme, plot, content, and mandate Children's literature teaching materials are usually widely used by students in the field of literature of children and lecturers of child literature.A process approach is a teaching-learning approach that leads to the development of basic physical and social skills to discover facts and concepts as well as developing attitudes and values through teaching and learning processes that have enabled students to grow a number of processes. Process approach is one way to practice language skills especially on writing skills. Children's literature materials are developed using process skills. This is done for the process of learning literature. Process skills can facilitate a person in making a literary work. Likewise with the literary work of children. one can create a literary work of a child by using a process skill. Children's literature teaching materials based on the literature teaching materials. This teaching material is designed by combining process skills with children literature materials. This instructional material is expected so that students can make beautiful children's literature and can be enjoyed by all society and not only among children